Childhood sun safety at different ages: relations between parental sun protection behavior towards their child and children's own sun protection behavior - Karlijn Thoonen; Francine Schneider; Math Candel; Hein de Vries; Liesbeth van Osch (BMC, 2019)
Abstract Background Sunburns during childhood are strongly associated with development of melanoma in later life. While parents play an important role in children's sun protection, insight in possible shifts in behavioral responsibility from parents towards their children and the possible effect of children's sex is important for targeting sun safety interventions throughout childhood and adolescence. Methods This cross-sectional survey study was conducted among a representative sample of Dutch parents (N = 1053) of children aged between 4 and 13 years old. Questionnaires measured both parental and children's own sun safety behavior during planned (e.g. going to the beach) and incidental (e.g. bycicling) sun exposure situations. Analyses of variance were used to test for age group differences and linear regression models were computed to detect behavioral shifts in executive behavior. Results Parents applied all sun safety behaviors (i.e. sunscreen use, wearing UV-protective clothing and seeking shade) more often on younger children, except for supportive behavior (facilitating children's own sun safety behavior), which remained relatively stable over the years. Older children and girls were more likely to execute sun safety behaviors themselves. A behavioral shift was found in wearing UV-protective clothing during planned situations among 11 year old children. For other behaviors, shifts were predicted after the age of 13. Conclusions Older children execute sun safety behaviors more often than younger children, although they still largely depend on their parents' protection. Specific attention for boys in the primary school years, and for both boys and girls in the years adjacent to adolescence is warranted in skin cancer prevention interventions.